Caribbean Political Economy at the Crossroads - Marshall, D. author. aut Link
XIV, 250 p.
Keywords: There are a variety of crisis symptoms confronting the Commonwealth Caribbean as the 21st century dawns. Global changes are quickly rendering the region's traditional economic platform obsolete. This book suggests however that the expanding NAFTA or the hemispheric turn towards bloc formation can offer a way out for the Caribbean. Politics must be brought back into the regionalisation process, for each island government is witnessing the narrowing of the range of its state power by powerful TNCs, international financial institutions, Washington interests, and corporate-backed WTO commissions.